1985
DOI: 10.1128/jb.163.2.774-777.1985
|View full text |Cite
|
Sign up to set email alerts
|

Heat and UV light resistance of vegetative cells and spores of Bacillus subtilis Rec-mutants

Abstract: The heat and UV light resistance of spores and vegetative cells of Bacillus subtiis BD170 (rec+) were greater than those of B. subtilis BD224 (recE4). Strain BD170 can repair DNA whereas BD224 is repair deficient due to the presence of the recE4 allele. Spores of a GSY Rec+ strain were more heat resistant than spores of GSY Rec-and Uvrmutants. The overall level of heat and UV light resistance attained by spores may in part be determined by their ability to repair deoxyribonucleic acid after exposure to these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 33 publications
2
6
0
1
Order By: Relevance
“…A higher induction of DNA damages by PL, such as pyrimidine dimer formation requiring the involvement of NER, could therefore be considered. Spores of the recA mutant strain were markedly more sensitive than 1A1 strain when exposed to PL, and also to UV‐C confirming previous observations .…”
Section: Discussionsupporting
confidence: 88%
“…A higher induction of DNA damages by PL, such as pyrimidine dimer formation requiring the involvement of NER, could therefore be considered. Spores of the recA mutant strain were markedly more sensitive than 1A1 strain when exposed to PL, and also to UV‐C confirming previous observations .…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that Bacillus spores are 10 to 20 times more resistant to UVC irradiation; 27 thus formation of spores can cause a suboptimal kill of Bacillus. Because freshly prepared bacteria cultures were used containing relatively low amounts of spores (as determined by specific staining of spores, data not shown), however, a higher resistance toward UVC irradiation of B. cereus itself compared to other bacteria is also a possible explanation 28,29 . Moreover, the UVC‐surviving bacteria were killed upon incubation at 80°C for 10 minutes, a treatment that spores will survive, also indicating that B. cereus itself has a higher resistance toward UVC.…”
Section: Discussionmentioning
confidence: 99%
“…Others have not found moist heat to be mutagenic, except for spores defective in SASP (see Setlow,this Symposium,. Deficiencies in DNA repair appear to cause spores to be more heat sensitive (Hanlin et al 1985). This finding suggests that heat-induced DNA damage can be repaired during germination and outgrowth and repairable DNA damage may not necessarily result in spore death.…”
Section: Nucleic Acidsmentioning
confidence: 98%